HOUT-18. COST EFFECTIVENESS OF TREATING GLIOBLASTOMA PATIENTS AGE 65 YEARS OR OLDER WITH TUMOR TREATING FIELDS PLUS TEMOZOLOMIDE VERSUS TEMOZOLOMIDE ALONE. (5th November 2018) - Guzauskas, Gregory; Wang, Bruce CM; Pollom, Erqi; Stieber, Volker W; Garrison, Lou
Abstract: BACKGROUND: TTFields plus TMZ treatment significantly increased five-year overall survival results compared to TMZ alone in all patients in the EF-14 trial, with the subgroup of patients age 65 and older showing the greatest survival benefit (hazard ratio 0.51 [CI 0.33–0.77]). This is the first report on the cost-effectiveness of TTFields in elderly GBM patients. METHODS: Patient outcomes were simulated using a 3-state area under the curve model. Survival was modelled over a lifetime horizon by integrating 5-year survival results of the EF-14 trial with long-term GBM epidemiology data and U.S. background mortality rates. Patient utilities from a previous publication were used to calculate quality-adjusted life years (QALYs). Adverse events of TTFields and TMZ were derived from the EF-14 trial for patients over 65 years, the costs from published literature. RESULTS: Elderly patients treated with TTFields and TMZ achieved mean lifetime survival of 3.66 years (3.04 years discounted). Patients treated with TMZ alone achieved a mean lifetime survival of 1.32 years (1.29 years discounted) The resulting incremental life years gained were 1.75 years discounted and the incremental quality-adjusted life years (QALYs) were 1.35. The incremental total cost was 192, 000. The ICER was 109, 500 per LYG and 142, 400 per QALY gained. The probability of TTFields being cost-effective was 85% at a willingness-to-pay threshold of 200, 000 per QALY. CONCLUSIONS: Treating newly diagnosed GBM patients over 65 years with TTFields and TMZ has the potential to increase mean lifetime survival and quality-adjusted survival substantially compared to TMZ alone. TTFields therapy, even when evaluated at its full list price, demonstrated high probability of cost-effectiveness at willingness-to-pay thresholds reported in economic literature for the United States. These results indicate that patients over age 65 may not only benefit from TTFields treatment, but also that their treatment may be cost-effective.